Factors Influencing the Development of Nairobi Securities Exchange - Kalui, Fredrick M.; Musya, Lucy Kalekye (European Scientific Journal, ESJ, 2019)
This study aimed to find out the factors influencing the development of the Nairobi Securities Exchange. The general objective of this study was to determine the factors that affect the development of the NSE. The specific objectives were to determine the effect of market information; market efficiency; market transparency; market openness; transaction processing system and operating/transaction cost; legal and regulatory framework on the development of the NSE. Both primary and secondary data collection methods were used. A semi- structured data collection questionnaire was used to collect primary data on institutional factors while secondary data was collected on market capitalization from 2006 to 2015 which was used as the indicator of NSE development. The study employed a descriptive research design to describe the empirical data. The population of study was all licensed stock brokers in the Nairobi Securities Exchange. A regression model was used for data analysis and hypothesis tested with a 0.05 significance level. This study concludes that market information, market efficiency, market openness, market transparency, transaction processing system and transaction/operating cost and legal and regulatory framework affects the development of Nairobi securities Exchange.The study recommends that developing countries to initiate policies to foster growth and development as countries liberalize their financial systems and further enhance domestic resource mobilization.